Anthropogenic impacts on mineral weathering: A statistical perspective - Pacheco, Fernando A.L.; Landim, Paulo M.B. [UNESP]; Szocs, Teodora (Elsevier, 2013)
Correspondence Analysis was adopted as tool for investigating the statistical structure of hydrochemical and weathering datasets of groundwater samples, with the main purpose of identifying impacts on mineral weathering caused by anthropogenic activities, namely fertilizing of farmlands. The hydrochemical dataset comprised measured concentrations of major inorganic compounds dissolved in groundwater, namely bicarbonate, silica (usually by-products of chemical weathering), chloride, sulphate and nitrate (typically atmospheric plus anthropogenic inputs). The weathering dataset consisted of calculated mass transfers of minerals being dissolved in loess sediments of a region located in SW Hungary (Szigetvár area), namely Na-plagioclase, calcite and dolomite, and of pollution-related concentrations of sodium, magnesium and calcium. A first run of Correspondence Analysis described groundwater composition in the study area as a system of triple influence, where spots of domestic effluents-dominated chemistries are surrounded by areas with agriculture-dominated chemistries, both imprinted over large regions of weathering dominated chemistries. A second run revealed that nitrification of N-fertilizers is promoting mineral weathering by the nitric acid reaction (anthropogenic pathway), in concurrence with the retreating of weathering by carbonic acid (natural pathway). It also indicated that dolomite and calcite are being players in a dedolomitization process driven by dissolution of gypsum fertilizers and nitrification of N-fertilizers. © 2013 Elsevier Ltd.
Keywords: Anthropogenic activity; Anthropogenic impacts; Anthropogenic inputs; Chemical weathering; Correspondence analysis; Groundwater composition; Mineral weathering; Statistical structures; Calcite; Carbon dioxide; Chlorine compounds; Fertilizers; Groundwater; Hydrochemistry; Inorganic compounds; Minerals; Nitrification; Sodium; Weathering; agricultural land; anthropogenic effect; calcite; correspondence analysis; dissolution; dolomite; dolomitization; effluent; fertilizer; hydrochemistry; loess; nitrification; plagioclase; silica; sodium; weathering; Hungary